Proses Penciptaan Manusia Perspektif Al-Qur’an dan Kontekstualitasnya dengan Ilmu Pengetahuan Sains: Kajian Kesehatan Reproduksi - Fitriani Fitriani; Esya Heryana; Raihan Raihan; Winona Lutfiah; Wahyudin Darmalaksana (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to analyze the contextuality between the Qur'an and science about the process of human creation. This study uses a qualitative method through a literature study, using a reproductive health theory approach and maudhu'i interpretation. The results and discussion of this study indicate that the process of human creation after Adam was through reproduction, among the phases are nuftah, 'alaqah, mudghah, bone formation, muscle formation, then perfected by blowing the spirit, until it becomes the best form. Meanwhile, in science, according to Sadler, the phases are gametogonesis, the process of ovulation to implantation, then the bilaminar gem disc, the embryonic period, to the time of delivery. According to Dudek, they are preferilization, weekly period, embryonic period, and organogenesis. This study concludes that the process of human creation in the Qur'an is in accordance with the findings of modern scientists today. This study recommends that the verses of science be revealed using a book of commentaries with a scientific style.